Cytotoxic labdane diterpenes from Hedychium ellipticum Buch.-Ham. ex Sm. - Songsri S. (2017)
© 2016 by the authors; licensee MDPI. In order to reveal the constituents and their biological activities, we carried out a phytochemical study on Hedychium ellipticum Buch.-Ham. ex Sm. (Zingiberaceae). Ten labdane diterpenoids (1-10) were isolated from the rhizomes of H. ellipticum for the first time. Their structures were identified on the basis of spectroscopic analyses including two-dimensional NMR and comparison with literature data. All of these compounds were evaluated for their antimycobacterial activity against Mycobacterium tuberculosis and cytotoxicity against KB, MCF7, NCI-H187 and Vero cells. The result showed that compounds 1 and 7 exhibited moderate activity against Mycobacterium tuberculosis and compounds 4, 6 and 7 displayed remarkable cytotoxic activity. This is the first report on the presence of all compounds in H. ellipticum and the first time that their structure activity relationship has been discussed.